Gandharva: Origin and Performing Arts - Dhakal, Bharat Raj (Journal of Development and Social Engineering, 2017)
The prime objective of this research article is to explore the different forms of arts performed by the ‘Gandharvas’ along with their historicity of social and sacred religious origin towards which the mainstream Nepali society is indifferent. In the social context of Nepal, they are regarded as the musician caste. They are also treated as the so-called lower caste people, the ‘dalits’ and are also denied the prestigious position in the society as well as in the pages of history. Although neglected in the society as well as in the history, they have got a pious origin as mentioned in the Hindu religious scriptures and beliefs. Their performing arts and musical instruments also have the religious significance. They have made a great contribution for nation through their performing arts. But the paradox is that they have not got the true recognition in Nepali society even though they share the sacred lineage like other groups. Although they have sacred place in religion, their position is downtrodden in society.